1959
DOI: 10.1177/004051755902900505
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Surface Barrier on Uptake Rates of Dye into Wool Fibers

Abstract: It is shown that any surface barrier to the entry of a dye into a fiber must modify the form of the uptake-time relation, the barrier exerting its greatest influence in the early stages of sorption, but becoming progressively less important as sorption proceeds. This is manifested by an initially concave-upwards tendency in the uptake-timel curve.The analysis, which takes account of variable diffusion characteristics of fibers forming the ~asemhly, is applied to the uptake of Naphthalene Orange G by wool, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1963
1963
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…It is also observed that the value of the intercept increases from 46.83 to 261.6 when C o is increased from 97 to 1187 mg/L, which indicates that the thickness of the boundary layer increases significantly with increase of C o . The multilinear nature of the intraparticle diffusion plots suggests the predominance of external mass transfer of MB at the beginning of adsorption [24]. The rate constants of external mass transfer were calculated using the plot of C/C o against time at different initial MB concentrations (figure not shown).…”
Section: Sorption Mechanismmentioning
confidence: 99%
“…It is also observed that the value of the intercept increases from 46.83 to 261.6 when C o is increased from 97 to 1187 mg/L, which indicates that the thickness of the boundary layer increases significantly with increase of C o . The multilinear nature of the intraparticle diffusion plots suggests the predominance of external mass transfer of MB at the beginning of adsorption [24]. The rate constants of external mass transfer were calculated using the plot of C/C o against time at different initial MB concentrations (figure not shown).…”
Section: Sorption Mechanismmentioning
confidence: 99%
“…On heating the dyebath to 90 °C in order to achieve fiber penetration, no significant effect of the plasma treatment on the extent of uptake or levelness of a relatively hydrophilic dye was observed as equilibrium conditions were approached. Extraction of normally scoured wool with lipid solvents also increases the dyeing rate (Medley & Andrews, 1959;Joko et al, 1985;Lindberg, 1953). This observation supports the concept that a lipid barrier to wool dyeing exists located at, or near, the fiber surface.…”
Section: Fig 1 Diffusion Pathways For Dyes Into Woolmentioning
confidence: 67%
“…Hampton and Rattee [4] used this relationship to study the surface barrier effects on wool dyeing. Medley [8] used the asymptotic equation of the semi-infinite model to study wool dyeing and used -D/a to indicate the surface barrier to wool dyeing as shown in Figure 1. The greater the value D/a, the greater the surface barrier effect on dyeing.…”
Section: Theoretical Model Used For Experimental Workmentioning
confidence: 99%